THE INFLUENCE OF PARENT-ADOLESCENT AND PEER INTERACTION ON PREMARITAL SEXUAL PERCEPTION OF BROKEN HOME ADOLESCENT - Qurrotul Aini; Yulina Eva Riany (Journal of Child, Family, and Consumer Studies, 2023)
Divorce in Indonesia continues to increase, resulting in an imbalance of family roles and functions. This imbalance has an impact on adolescents such as adolescent premarital sexual behavior. The purpose of this study is to identify the relationship and influence of parent-adolescent interaction and peer interaction on the perception of premarital sexuality in adolescents from broken home families. The method used in this study was purposive sampling method with online survey completion. The number of research samples was 190 adolescents from broken home families in the Jabodetabek area (Jakarta, Bogor, Depok, Tangerang and Bekasi). The relationship test shows that parent-adolescent interaction has a significant negative relationship with the premarital sexual perceptions of adolescents from broken home families. The results of the effect test show that parent-adolescent interaction has a significant negative effect on the premarital sexual perceptions of adolescents from broken home families, but peer interaction has a positive and insignificant effect on the sexual perceptions of adolescents from broken home families. It is expected that parents can be a discussion partner for adolescents in solving problems. Teenagers are expected to be able to choose a good friendship environment.